Protein assemblies of sodium and inward rectifier potassium channels control cardiac excitability and arrhythmogenesis - Willis, B. Cicero (Am J Physiol Heart Circ Physiol, 2015)
The understanding of how cardiac ion channels function in the normal and the diseased heart has greatly increased over the last four decades thanks to the advent of patch-clamp technology and, more recently, the emergence of genetics, as well as cellular and molecular cardiology. However, our knowledge of how these membrane-embedded proteins physically interact with each other within macromolecular complexes remains incomplete. This review focuses on how the main cardiac inward sodium channel (Na(V)1.5) and the strong inward rectifier potassium channel (Kir2.1) function within macromolecular complexes to control cardiac excitability. It has become increasingly clear that these two important ion channel proteins physically interact with multiple other protein partners and with each other from early stages of protein trafficking and targeting through membrane anchoring, recycling, and degradation. Recent findings include compartmentalized regulation of Na(V)1.5 channel expression and function through a PDZ (postsynaptic density protein, Drosophila disc large tumor suppressor, and zonula occludens-1 protein) domain-binding motif, and interaction of caveolin-3 with Kir2.1 and ankyrin-G as a molecular platform for Na(V)1.5 signaling. At the cardiomyocyte membrane, Na(V)1.5 and Kir2.1 interact through at least two distinct PDZ domain-scaffolding proteins (synapse-associated protein-97 and α(1)-syntrophin), thus modulating reciprocally their cell-surface expression at two different microdomains. Emerging evidence also shows that inheritable mutations in plakophilin-2, ankyrin-G, dystrophin, syntrophin, synapse-associated protein-97, and caveolin-3, among others, modify functional expression and/or localization in the cardiac cell of Na(V)1.5, Kir2.1 or both to give rise to arrhythmogenic diseases. Unveiling the mechanistic underpinnings of macromolecular interactions should increase our understanding of inherited and acquired arrhythmogenic cardiac diseases and may lead to advances in therapy.